Workload, Recognition, and Environment: Key Drivers of Employee Stress – A Case Study at PT PLN Unit X - Afrianda, Dr. Rio (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
Work-related stress is a crucial factor in business, primarily due to its connection with employee performance. A company must perform well to generate profit, and high performance is the ideal. Conversely, declining performance can harm the business. Undoubtedly, every employee will experience some level of job-related stress. This study collected quantitative data through questionnaires and interviews. Validity tests, the coefficient of determination test, partial hypothesis testing, and classical assumption tests were employed to evaluate the variables. The research was conducted at PT PLN Unit X with a sample of 83 respondents. Data were analyzed using multiple linear regression with SPSS 20 for Windows. The main objective of this study is to identify the key factors contributing to employee stress and provide a foundation for the company to take appropriate action in managing stress and improving employee well-being. The findings reveal that workload, lack of appreciation, and work environment have a positive and significant impact on job stress, categorized as very strong. PT PLN Unit X aims to reduce employee stress levels to an ideal point that enables maximum performance by improving both financial and non-financial aspects of employee well-being.